2015
DOI: 10.1097/pcc.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Pediatric Critical Care Focused Bedside Ultrasound Training Program in a Large Academic PICU*

Abstract: Implementation of a critical care bedside ultrasound program for critical care providers in a large academic PICU is feasible. Bedside ultrasound evaluation and interpretation by intensivists affected the management of critically ill children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 21 publications
1
56
0
Order By: Relevance
“…Among the studies reporting on the effects of training attending clinicians to perform POCUS, the application of POCUS was considered to contribute to changes in management in 16–37% of cases in different clinical contexts . Studies reported similar findings after training residents or fellows, with POCUS contributing to management changes in 16–40% of clinical applications . Only one study evaluated any impact on patient‐relevant outcomes of training medical students to perform POCUS, demonstrating improved safety of simulated central venous catheter placement using ultrasound …”
Section: Resultsmentioning
confidence: 99%
“…Among the studies reporting on the effects of training attending clinicians to perform POCUS, the application of POCUS was considered to contribute to changes in management in 16–37% of cases in different clinical contexts . Studies reported similar findings after training residents or fellows, with POCUS contributing to management changes in 16–40% of clinical applications . Only one study evaluated any impact on patient‐relevant outcomes of training medical students to perform POCUS, demonstrating improved safety of simulated central venous catheter placement using ultrasound …”
Section: Resultsmentioning
confidence: 99%
“…Though the length and components of sonographer training as well as assessments of proficiency generally were not reported in these studies, learning US for ETT verification seems consistent with current literature suggesting that short application-focused US training regimens can be effective. [24][25][26] Chowdhry et al published the successful training of 12 US technicians in this application with a one-time 1-hour session by a pediatric radiologist. 17 Sethi et al reported training of their sonographer for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…15 Institutional credentialing is desirable however, and methods for credentialing are being developed. 16 Risk assessment for patients undergoing fetal surgery can be difficult because of limited experience and the questionable applicability of typical risk indices to this patient population. In this case, the fetus had a Chiari II malformation with a slight hindbrain herniation and large myelomeningocele likely to result in incontinence and weakness of the lower extremities.…”
Section: Discussionmentioning
confidence: 99%